(untitled) (Psychology Travelogs, 2021)
The article presents an analysis of psychological and pedagogical research on the features and current state of psychological rehabilitation of servicemen after service in combat. The content of the concept of psychological rehabilitation as a process of organized psychological influence aimed at helping servicemen to overcome the negative psychological consequences of traumatic stress of military activities, to ensure such a state of mental health of servicemen, which allows them to solve combat and service tasks. The concept of psychological assistance as a set of psychological, organizational, medical and other measures aimed at ensuring the successful overcoming by soldiers of the circumstances of modern combat, traumatizing the psyche in order to maintain combat effectiveness and prevent the development of post-traumatic mental disorders. The stages of providing psychological assistance and rehabilitation to servicemen are revealed. The tasks of psychological rehabilitation of a serviceman are determined by the nature of traumatic stress, among which the central place is occupied by combat stress. The implementation uses the basic principle - taking into account and taking into account the individual psychological characteristics of each wounded and their compliance with the main objectives of socio-psychological rehabilitation. The provision of primary psychological care should be accompanied by a skilful psychotherapeutic conversation of the unit commander, personnel officer, psychologist after the acute reaction to BPT is removed and the victim becomes capable of reasonable action again. The realization that a member of the military is literally fighting the enemy, and that he is generally physically healthy in the rear, is a powerful motive and incentive for most servicemen to return to the unit.